Commodifying Renewable Energy Communication for Indonesia’a National Resilience (Jurnal Lemhannas RI, 2025)
Purpose: This study examines how the @kementerianpu Instagram account commodifies New and Renewable Energy (NRE) messages through verbal and visual representation and how this communication relates to national resilience.Methodology: A descriptive qualitative approach within an interpretive paradigm guided virtual observation and documentation of NRE-related Instagram content. Purposive sampling selected a floating solar power plant carousel as the primary analytical case, with visible audience responses as supplementary evidence. Data were analysed using Kress and van Leeuwen’s multimodal discourse framework.Findings: The messages related to renewable energy delivered have been implemented consistently in visual information, sustainability symbols, and simplification of policy narratives, thus shaping public perception and strengthening the legitimacy role of energy communication as part of national resilience.Originality: The study integrates Mosco’s media commodification perspective with Kress and van Leeuwen’s multimodal discourse framework to explain how government institutions compete for digital attention while constructing renewable energy policy meaning within the broader framework of national resilience.
Keywords: Digital Communication; National Resilience; Renewable Energy; Social Media; Visual Commodification